2007
DOI: 10.1097/01.olq.0000258339.17325.93
|View full text |Cite
|
Sign up to set email alerts
|

Viagra, Methamphetamine, and HIV Risk: Results From a Probability Sample of MSM, San Francisco

Abstract: MSM who use Viagra with crystal methamphetamine have high prevalence rates of HIV and engage in HIV risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 14 publications
5
40
0
1
Order By: Relevance
“…6,21 Moreover, among HIV-infected MSM with a serodiscordant (HIV-uninfected or unknown HIV status) sexual partner, crystal meth use is significantly associated with UAI (insertive: odds ratio [OR] 1.9, 95% confidence interval [CI] 1.1-3.3; receptive: OR 1.6, 95% CI 0.9-3.1). 22 This has been corroborated by multiple studies. [23][24][25] There are subgroups within this community with variable patterns of crystal meth use that engage in behaviors that are at particularly high risk for HIV transmission and STI acquisition.…”
Section: Hiv Risk Behaviorsupporting
confidence: 65%
“…6,21 Moreover, among HIV-infected MSM with a serodiscordant (HIV-uninfected or unknown HIV status) sexual partner, crystal meth use is significantly associated with UAI (insertive: odds ratio [OR] 1.9, 95% confidence interval [CI] 1.1-3.3; receptive: OR 1.6, 95% CI 0.9-3.1). 22 This has been corroborated by multiple studies. [23][24][25] There are subgroups within this community with variable patterns of crystal meth use that engage in behaviors that are at particularly high risk for HIV transmission and STI acquisition.…”
Section: Hiv Risk Behaviorsupporting
confidence: 65%
“…There is an extensive literature on non-injection drug use and HIV risk behavior in MSM populations elsewhere in the world. Many studies have found associations between sexual risk behavior and consumption of recreational drugs including crystal methamphetamine, ecstasy, cocaine, gamma hydroxybutyrate (GHB), and amyl nitrate (''poppers'') in a variety of social contexts (Choi et al 2005;Colfax et al 2001;Darrow et al 2005;Hirshfield et al 2004;Koblin et al 2006;Operario et al 2006;Rawstorne et al 2007;Spindler et al 2007;Stueve et al 2002). One study has described sexual risk behavior among members of drug-using sub-populations of urban South African MSM (Parry et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…These findings differ from the majority of previous studies on this topic. One of the most plausible reasons for the varying conclusions is that the focus of our study is on men who received EDD as part of clinical practice, whereas nearly all of the previous reports linking EDD to risky sexual behavior were conducted in non-clinical samples in high risk groups, including MSM [4][5][6][7][8][9][10][11][12]16,25 , substance abusers 11,26 , and HIV-infected men outside of clinical settings. [13][14][15] In nearly all of these studies, the association of EDD and risky sexual behavior was consistently the strongest in men who also used stimulant drugs such as methamphetamines, ecstasy, or gamma-hydroxybutyrate (GHB), which were rare in our study sample.…”
Section: Discussionmentioning
confidence: 64%
“…3 EDDs have also been linked to high-risk sexual behavior in some groups of men at increased risk for HIV transmission, in particular men who have sex with men (MSM), men who use recreational or illicit drugs, and HIV-infected men. [4][5][6][7][8][9][10][11][12][13][14][15][16] Because of their association with risky behavior, some have argued that EDD medications should be classified as controlled substances.…”
Section: Introductionmentioning
confidence: 99%